Metaverse Land Purchasing in Agreement Legal Perspective - Sopamena, Ronald Fadly (Batulis Civil Law Review, 2023)
In Indonesia, the term metaverse is widely discussed when many people buy metaverse land. On the Nextearth.io site, a number of virtual lands on a digital map of the location of a number of important areas or assets in Jogjakarta have also been sold for the value of crypto currency. This is a little different because the land purchased is not land in the real world but land that only exists in the virtual world. the research objective is the mechanism and validity of land sale and purchase agreements in the metaverse. This research is normative legal research using a normative juridical method using a law approach as a source of law and supporting literature. Purchase of land in Metaverse can be done by accessing the website which is a platform used for virtual property transactions. If reviewing the agreement on the purchase of metaverse land, the sale and purchase agreement is valid because it fulfills the legal requirements of the agreement.